2007
DOI: 10.1259/dmfr/98032356
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional and cone beam CT synthesized cephalograms

Abstract: CBCT can reproduce conventional cephalometric geometry with similar precision and accuracy. Orthogonal CBCT projections provided greater accuracy of measurement for midsagittal plane dimensions than perspective CBCT or conventional cephalometric images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
143
2
30

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(195 citation statements)
references
References 32 publications
2
143
2
30
Order By: Relevance
“…10 The CBCT images allow clinicians to evaluate the size of the alveolar bones without the disadvantages of conventional radiographs, as these images give accurate measurements as a result of the high clarity, with the possibility of extracting cephalogram images with accuracy and reliability. [11][12][13] Several studies in the orthodontic literature have focused on the relationship between the thickness of anterior alveolus and the labiolingual position of upper and lower incisors; the relationship between different skeletal jaw positions and anterior alveolar thickness has also been evaluated. 6,8,[14][15][16] In the study of Kim et al, vertical alveolar bone levels and alveolar bone thickness were compared between lower and upper incisors in surgical skeletal class III patients; they found that the amount of bone loss at the lower incisors was greater than that of the uppers, and lingual bone thickness was greater at the upper incisors and smaller at the opposing teeth.…”
Section: Jcdpmentioning
confidence: 99%
“…10 The CBCT images allow clinicians to evaluate the size of the alveolar bones without the disadvantages of conventional radiographs, as these images give accurate measurements as a result of the high clarity, with the possibility of extracting cephalogram images with accuracy and reliability. [11][12][13] Several studies in the orthodontic literature have focused on the relationship between the thickness of anterior alveolus and the labiolingual position of upper and lower incisors; the relationship between different skeletal jaw positions and anterior alveolar thickness has also been evaluated. 6,8,[14][15][16] In the study of Kim et al, vertical alveolar bone levels and alveolar bone thickness were compared between lower and upper incisors in surgical skeletal class III patients; they found that the amount of bone loss at the lower incisors was greater than that of the uppers, and lingual bone thickness was greater at the upper incisors and smaller at the opposing teeth.…”
Section: Jcdpmentioning
confidence: 99%
“…To date, multiple ex vivo studies have attempted to establish the ability of CBCT images to accurately reproduce the geometric dimensions of the maxillodental structures and the mandible. [22][23][24][25] A relatively low patient dose for dedicated dentomaxillofacial scans is a potentially attractive feature of CBCT imaging. The dosing characteristics of dentomaxillofacial scanners were discussed in Part 1 of this series.…”
Section: Dentomaxillofacial Imagingmentioning
confidence: 99%
“…29,31,32 Several studies have described the 3D geometric accuracy of CBCT imaging in the maxillodental and mandibular regions as well. [22][23][24][25] Examples of CBCT imaging studies for implant planning and visualization of the mandibular canal are presented in Figures 1 and 2 respectively.…”
Section: Implantologymentioning
confidence: 99%
“…The advantages of CBCT over conventional CT or dental films include low radiation dose, lower cost, excellent tissue contrast, elimination of blurring and overlapping of adjacent teeth, and high spatial resolution. [14][15][16][17][18] The goal of this study was to evaluate the vertical alveolar bone levels and thickness around the maxillary and mandibular incisors of adult skeletal Class III patients by using 3-D CBCT images. The hypothesis of this study was that the bone loss is not different in the maxillary and mandibular incisors.…”
Section: Introductionmentioning
confidence: 99%